Control-oriented modeling and real-time simulation method for a dual-mode scramjet combustor. (December 2018) - Ma, Jicheng; Chang, Juntao; Zhang, Junlong; Bao, Wen; Yu, Daren
Abstract: The control-oriented modeling and real-time simulation method for a dual-mode scramjet combustor has been conducted in this paper. The 1-D unsteady model coupled with isolator shock train model and oblique shock wave modification can treat variable area, fuel addition, combustion heat release, variable specific heat, inflow air vitiation component, wall friction and mixing efficiency. Combustion is simplified into mass and heat addition process. So this paper discusses heat release distribution obtaining method which can be applied in scramjet combustor 1-D flowfield simulation in detail. It is fit for certain scramjet combustor configuration and acceptable over a wide range of inflow conditions. By mixed programming of C and Matlab, the code of model solving is capsuled into S-Function which can be used in SIMULINK. The control-oriented model is built on SIMULINK platform. When the model runs in a single-core 3.6 GHz Intel Core i7-4790 processor, computation time-consuming is found to require 5–10 ms within a control period. The computing speed indicates very promising, because model is compact enough to run in real time, and it can be used as an embedded model in control system research. This model can also be used to analyze unsteady and steady flowfield characteristic. The safety boundary codetermined by unstart and over-temperature is conducted using this model. Highlights: Control-oriented 1-D unsteady model was presented for dual-mode scramjet combustor. By mixed programming, real-time model was built on SIMULINK platform. The heat release distribution obtaining method was discussed and explained. The unsteady, steady flowfield process and safety boundary were analyzed.